HUBUNGAN DAYA TAHAN DAN KELINCAHAN DENGAN KEMAMPUAN MENGGIRING BOLA TIM SEKOLAH SSB SEPAKBOLA CHEVRON RUMBAI KECAMATAN RUMBAI PESISIR - Puji Susanto; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is conducted to see any possible relation between endurance and agility with the ability to dribble the ball on the players of Chevron SSB School Football Team in Rumbai Pesisir District. The sample used in this research is a team of 20 football players of Chevron SSB School Football Team in Rumbai Pesisir District. The sampling method of this research is total sampling using all 20 players of Chevron SSB School Football Team in Rumbai Pesisir District. The result of the first analysis shows a strong relation between the endurance (X1) of the players and their ability to dribble the ball (Y) where is on significance level of ɑ (0.05) = (0,834) > (0.456), which means hypothesis is accepted. Meanwhile, the calculation of the second analysis also shows a strong relation between the agility (X2) of the players and their ability to dribble the ball (Y) where is on significance level of ɑ (0.05) = (0,943) > (0.456) which means hypothesis is accepted too. Lastly, on the third analysis to see the relation between endurance (X1) and agility (X2) toward the ability to dribble the ball (Y) where is on significance level of ɑ (0.05) = (0,938) > (0.456), it can be concluded that endurance (X1) and agility (X2) are strongly related to the ability to dribble the ball (Y). Keywords: Endurance, Agility, Dribble.